Concurrent ring-opening and atom transfer radical polymerization for synthesis of block copolymers, and their comprehensive chromatographic characterization. (5th January 2021) - Ahmad, Tehsin; Durrani, Sidra Safdar; Iftikhar, Faiza Jan; Musharraf, Syed Ghulam; Malik, Muhammad Imran
Graphical abstract: Highlights: Concurrent ring-opening and atom transfer radical polymerization. Synthesis of block copolymers of styrene and L-lactide. Comprehensive chromatographic characterization in context of parallel polymerization mechanisms. Characterization of PS-b-PLA by SEC, NMR, LCCC, GEPC, and two-dimensional LC. Abstract: In this study, we report concurrent ring-opening and atom transfer radical polymerization for synthesis of the block copolymers of L-lactide and styrene. Simultaneous polymerization of two different polymerization mechanisms requires careful selection of reaction conditions and reagents for targeted comparable propagation of both types. Several different di-block copolymers are synthesized having different total molar mass, chemical composition, and individual block lengths. Such simultaneous polymerization mechanisms require different reagents, and the regents required for one type of polymerization may hamper the other parallel mechanism. Hence, synthesized block copolymers are analysed comprehensively using different polymer chromatographic techniques and NMR spectroscopy. Total molar mass and chemical composition of BCPs are determined by size exclusion chromatography and NMR, respectively. PLA block length in PS-b-PLA and quantification of PS homopolymers is revealed by liquid chromatography at critical conditions of PS. For determination of PS block length in PS-b-PLA and quantification of PLA homopolymers, a gradient polymer elution chromatography (GPEC) method is applied. The comprehensive analysis of synthesized PS-b-PLA by parallel polymerization mechanisms revealed uninterrupted simultaneous polymerization of both monomers under applied conditions.